A Study on the Impact of China’s Monetary Policy on Economic Development - Tan Yuxiu (SHS Web of Conferences)
At present, China’s national economy is in a stable recovery phase and is undergoing structural transformation and upgrading. At this historic key point, monetary policy, as a vital macroeconomic regulatory instrument, exerts an immensely significant role in promoting national economic development. Amidst China’s pursuit of high-quality economic development and the ongoing refinement of its market system, the effect and influence of the implementation of monetary policy is increasingly being paid attention to. This paper will start from the relevant concepts of monetary policy, and by sorting out the tools, roles, economic principles, and relationship with economic development of monetary policy, its objective is to elucidate the pathways and impacts of monetary policy on pivotal economic indicators, such as economic growth, commercial credit, employment, etc. It puts forward policy recommendations such as improving monetary policy tools, strengthening the coordination between monetary policy and fiscal policy, and improving the transparency of monetary policy, with a view to providing theoretical basis and practical reference for China’s macroeconomic regulation.